2009
DOI: 10.1063/1.3148267
|View full text |Cite
|
Sign up to set email alerts
|

Direct growth of transparent conducting Nb-doped anatase TiO2 polycrystalline films on glass

Abstract: This paper proposes a novel sputter-based method for the direct growth of transparent conducting Ti1−xNbxO2 (TNO) polycrystalline films on glass, without the need for any postdeposition treatments, by the use of an initial seed-layer. Anatase TNO epitaxial films grown on LaAlO3 (100) substrates under a reducing atmosphere exhibited a low resistivity (ρ) of (3–6)×10−4Ωcm. On glass, however, highly resistive rutile phase polycrystalline films (ρ∼100Ωcm) formed preferentially under the same conditions. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…Nb‐doped anatase TiO 2 (TNO) is a newly developed TCO with unique properties, such as excellent chemical stability , high refractive index , and wide conductivity range . Since the discovery of TNO grown by pulsed laser deposition (PLD) , many efforts have been dedicated to fabricate highly conductive TNO on glass substrates with a scalable and industrial deposition method, that is, sputtering . In our previous studies using PLD and sputtering , we observed that TNO films crystallized from amorphous precursors that were deposited on unheated substrates, exhibited high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nb‐doped anatase TiO 2 (TNO) is a newly developed TCO with unique properties, such as excellent chemical stability , high refractive index , and wide conductivity range . Since the discovery of TNO grown by pulsed laser deposition (PLD) , many efforts have been dedicated to fabricate highly conductive TNO on glass substrates with a scalable and industrial deposition method, that is, sputtering . In our previous studies using PLD and sputtering , we observed that TNO films crystallized from amorphous precursors that were deposited on unheated substrates, exhibited high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the difficulties, much effort has been devoted to the growth of its thin films via a variety of methods, such as the magnetic sputtering [8], molecular beam epitaxy [9], and pulsed-laser deposition [10], where the nature of the film/substrate interface has long been suspected to play an important role in affecting the crystallinity of the thin films. To date, TiO 2 thin films have been deposited onto a wide range of oxide substrates, involving, e.g., the yttria-stabilized zirconia (YSZ) [11], Al 2 O 3 [12], SiO 2 [13], SrTiO 3 (STO) [14], and LaAlO 3 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our initial work used SnO x :F [4][5][6][7], and more recently we have investigated SSRs based on anatase TiO 2 :Nb [8,9]. This latter material was discovered as lately as 2005 [13] and has attracted much interest recently as a high-performance low-cost transparent conductor [14][15][16][17][18]. Our earlier work demonstrated that TiO 2 :Nb backed by Al leads to a reflector with pronounced optical selectivity [8,9].…”
Section: Introductionmentioning
confidence: 99%